The relationship between neutrophil to lymphocyte ratio (NLR) at admission and GRACE mortality risk score in acute myocardial infarction patient at Tabanan Regency Hospital in 2017 - Gede Wikananda; Eka Ariawan; Michelle Husin (DiscoverSys Inc., 2019)
Background: This study aimed to investigate the role of neutrophil to lymphocyte ratio (NLR) as non-specific and independent laboratory biomarkers when associated with Global Registry of Acute Coronary Events (GRACE) mortality risk score in predicting the morbidity and mortality of patient with acute myocardial infarction (AMI).Methods: A cross-sectional study design among 103 AMI patients who met inclusion criteria were enrolled in this study. NLR was the ratio of absolute count between neutrophil and lymphocyte. In addition, the GRACE score was a valid instrument in evaluating acute coronary syndrome (ACS). Data were analyzed using SPSS software version 17.Results: Correlation test showed a weak positive correlation between NLR value and GRACE risk score (r=0,388; p<0,05). Bivariate comparative analysis showed that there was a significant difference in NLR mean in GRACE score group (F (2,100) =5,215, p=0,007). Using the least significance different, it was found that there was a significant difference of NLR mean between low and high GRACE score group (p=0,003; 95% CI =-3,556 – (-0,736).Conclusion: Our study suggests that there was an increase in NLR value proportional to the higher GRACE stratification risk score and there was a significant difference between NLR values in low and high GRACE groups.